Complex multisource sound induces greater neurodegeneration in neonatal rat brain than single-source sound - Daltaban, İskender Samet; Aydın, Mehmet Dumlu; Eyüpoğlu, Eylem Eren; Demirci, Elif; Okuyan, Aybike Aydin; Demir, Mehmet Emin (Frontiers in Systems Neuroscience, 2026)
BackgroundExcessive noise exposure is a known environmental health hazard linked to neurological injury and cognitive deficits. Whether complex sound waveforms from multiple sources exacerbate brain damage compared to a single-source noise of equal intensity remains unclear. We investigated the effects of identical music played either through one or four loudspeakers on the developing brain of newborn rats.MethodsForty-one newborn Sprague–Dawley rat pups (both sexes), along with their dams, were randomly assigned to three groups: control (no noise, n = 6), single-speaker exposure (n = 15), and multi-speaker exposure (n = 20). From postnatal day 0 to 30, the exposure groups were subjected to an 8-min music track (~85 dB SPL) either via one loudspeaker (simple waveform) or simultaneously via four loudspeakers (complex interfering waveform), six times daily at 4-h intervals. Sound intensity was calibrated at the cages with a sound-level meter. All procedures followed ARRIVE guidelines and the EU Directive 2010/63/EU for animal research, with institutional ethical approval. After 1 month, rat brains were examined histologically. Unbiased stereology was used to estimate neuronal densities in the temporal lobe (including amygdala and hippocampal dentate gyrus). Immunohistochemistry for neuron-specific enolase (NSE), glial fibrillary acidic protein (GFAP) and TUNEL assay (terminal deoxynucleotidyl transferase dUTP nick-end labeling) was performed to identify neuronal integrity, astroglial response, and apoptosis, respectively. Outcome measures were degenerated (TUNEL-positive) neuron densities and histopathological lesions. Statistical comparisons were made using Student’s t-tests or ANOVA and chi-square tests (with p < 0.05 considered significant).ResultsEight of 20 pups (40%) in the multi-speaker group died during the exposure period, compared to 5/15 (33%) in the single-speaker group and 3/6 (50%) in controls (differences not statistically significant). Maternal rats exhibited agitation, stress behaviors, and weight loss under noise; some eventually ceased escape attempts (habituation/helplessness behavior) in both noise-exposed groups. Histologically, the multi-speaker exposure caused more severe brain injury than the single-speaker exposure. Pups in the multi-speaker group showed frequent subarachnoid hemorrhages and cortical microvascular bleeding in the temporal lobes, whereas these lesions were mild or infrequent in the single-speaker group and absent in controls. Neurons in noise-exposed brains displayed morphological signs of degeneration (shrunken, angulated cell bodies with pyknotic nuclei and condensed cytoplasm), which were markedly pronounced in the multi-speaker group. Stereological cell counting revealed a significant increase in apoptotic neuron density in both sound-exposed groups, with the multi-speaker group highest. For example, in the hippocampal dentate gyrus, the mean density of TUNEL-positive (degenerating) neurons was 13,450 ± 1,560 per mm3 in the multi-speaker group vs. 7,600 ± 980 per mm3 in the single-speaker group and only 200 ± 34 per mm3 in unexposed controls (p < 0.05). In the amygdala, apoptotic neuron density averaged 3,460 ± 863 per mm3 (multi-speaker) vs. 1,470 ± 285 (single-speaker) and 1,321 ± 234 (control), with the multi-speaker group showing a significantly higher burden of neuronal cell death (p < 0.005 for complex vs. simple waveforms). Correspondingly, multi-speaker exposed brains showed intense immunostaining for NSE and GFAP fragmentation, indicating widespread neuronal loss and reactive astroglial injury, whereas single-speaker exposure caused only moderate changes.ConclusionIdentical musical noise caused substantially more neurodegeneration in the developing brain when delivered as complex wave interference from multiple speakers rather than as a single-source sound of the same intensity. Complex multisource waveforms appear to amplify the harmful effects of noise on neonatal brain tissue, likely through interference-driven pressure fluctuations. These findings have clinical and public health implications, suggesting that current noise exposure guidelines should consider not only sound intensity and duration but also the acoustic complexity and source configuration, especially to protect vulnerable populations such as infants and children from high-intensity multisource noise environments.